Structural Perspectives of Insulin Receptor Isoform-Selective Insulin Analogs - Jiráček, Jiří; Žáková, Lenka (Frontiers in Endocrinology, 2017)
A significant drawback of the exogenous administration of insulin to diabetics is the non-physiological profile of insulin action resulting in the insufficient suppression of hepatic glucose production, which is the main contributing factor to diabetic hyperglycemia under fasting conditions and the basis of the challenge to restore a more physiological glucose profile in diabetes. The insulin receptor (IR) exists in two alternatively spliced variants, IR-A and IR-B, with different tissue distribution. While peripheral tissues contain different proportions of both isoforms, hepatic cells almost exclusively contain IR-B. In this respect, IR-B-selective insulin analogs would be of great interest for their potential to restore more natural metabolic homeostasis in diabetes. Recent advances in the structural biology of insulin and IR have provided new clues for understanding the interaction of both proteins. This article discusses and offers some structural perspectives for the design of specific insulin analogs with a preferential binding to IR-B.